Wings of gold : the story of the first women naval aviators - Weintraub, Beverly, 1961- (Lyons Press, an imprint of Globe Pequot, the trade division of The Rowman & Littlefield Publishing Group, Inc., 2021)
"This is the story of the first women naval aviators and their struggles and triumphs as they earned their Wings of Gold, learned to fly increasingly sophisticated jet fighters and helicopters, mastered aircraft carrier landings, served at sea, and reached heights of command that would have been unthinkable less than a generation before. It is also the story of the legacy they left behind"--